The use of CLO3D application in vocational school fashion expertise program: Innovations, challenges and recommendations - Prasetya, Luhur Adi; Widiyawati, Irva; Rofiudin, Amir; Haq, Salsabila Thifal Nabil; Hendranawan, Rian Syahmulloh; Permataningtyas, Anisa; Ichwanto, Muhammad Aris (Univeritas Papua, 2025)
This study examines the effectiveness of using CLO3D application in learning fashion design in vocational schools. CLO3D is a three-dimensional design simulation software that allows students to explore fashion design virtually, accelerate the learning process, and enhance creativity. This study used systematic literature review method with PRISMA approach, analyzing 20 articles identified from various indexed international journals. The analysis showed that 85% of the studies reported significant improvement in students' design visualization ability, while 75% of the studies demonstrated time efficiency and reduced need for physical prototyping. A total of 70% of the articles revealed that CLO3D encouraged student creativity through more in-depth design exploration. However, the main challenges identified included a lack of teacher training (65%) and infrastructure limitations, particularly high-specification hardware. This study concludes that CLO3D has great potential in supporting fashion learning in vocational schools if supported by educator training and adequate infrastructure provision. The implication of this research is to encourage wider integration of 3D simulation-based technology in vocational education to support a more effective and innovative learning process.